Dvazhdy Geroy Sovetskogo Soyuza podpolkovnik Stepan Pavlovich SUPRUN (Изобразительное искусство, 1941)
Portrait of Soviet soldier lieutenant-colonel Stepan Pavlovich Suprun with flag of Soviet Union and Soviet air-force behind Original title: Дважды Герой Советский Союз Подполковник Степан Павлович СУПРУН. Suggested translation: Twice Hero of the Soviet Union lieutenant-colonel Stepan Pavlovich SUPRUN PO-0031